ANALYSIS OF KEYWORDS OF SCIENTIFIC PRODUCTION OF RESEARCHERS: THE AUTHOR AS AN INDEXER - Fujita, Mariângela Spotti Lopes [UNESP]; Tartarotti, Roberta Cristina Dal’Evedove [UNESP] (Universidade Estadual de Londrina, 2025)
Introduction: With the advent of the digital and web era, the keyword has become an essential representation product in open access information storage and retrieval systems. It is used in the extraction functions for the purpose of scientific identification of authors, bibliometric analysis, indicators of scientific impact, development of controlled vocabularies and other systems of knowledge organization. The attribution of keywords by the author in scientific publications is a practice of representing the content carried out when filling in metadata. This assignment goes through personalized subject analysis and depends on the author's specialty vocabulary, which, in general, has no guidance on standardization and vocabulary control. On the other hand, such subject metadata that receives the keyword does not undergo professional validation. Objective: Analysis of keywords assigned by researchers to submit articles from journals indexed in Scopus and in the Portal Professores Unesp regarding the standardization and vocabulary control for different functions in information storage and retrieval systems. Methodology: For this purpose, an exploratory research was carried out with an observation study and analysis of keywords attributed by researchers from Portal Docentes Unesp based on data from the CNPq Lattes Curriculum compared to keywords attributed to journal articles. Results: The results demonstrate an absence of standardization in the keywords of the journal articles of researchers registered in the Lattes Curriculum, both at syntactic and semantic level. Regarding the assessment of indexation, low levels of consistency are observed when compared to the original articles, both in the rigid index and in the relaxed / flexible index. Conclusions: There is a need to develop a policy for organizing and representing information that provides guidelines to researchers regarding the attribution of keywords, aiming at greater standardization and consistency both in the representation and in the recovery of their scientific production.
ANÁLISE DE PALAVRAS-CHAVE DA PRODUÇÃO CIENTÍFICA DE PESQUISADORES: O AUTOR COMO INDEXADOR
Keywords: Control of vocabulary; Controlled vocabulary; Indexing; Lattes Curriculum; Scientific production